Initial Coin Offering (ICO) in Perspective Law of Sharia Business - Subarkah, Imam (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Tixl (TXL) is a crypto money project that uses Initial Coin Offering (ICO) to fund its development phase. Various problems underlying the existence of Tixl (TXL) and the proposed solutions are closely related to the condition of society in the information technology era. This study aims to determine the various factors underlying the use of ICO as a way to raise funds, examine Tixl (TXL) as a crypto money project and its position in public life which is reviewed in the perspective of the maá¹£laá¸¥a mursala, and token sales transactions in ICO organized by Tixl gmmbH in the perspective of Islamic treaty law. This research is a library research using a conceptual approach and qualitative analysis techniques. This paper shows that there are three factors underlying the use of ICOs as a way to raise funds, namely a change in orientation in the business model, tokenization, and characteristics of business activities. As a crypto money project, Tixl (TXL) cannot provide benefits that are comprehensive or kully, even the harm caused is greater than the benefits. Transaction of token sales in ICO held by Tixl (TXL) is a transaction that is damaged because it is contrary to maqÄá¹£id al-sharÄ«'ah.